The Enduring Influence of Taboos in Social Regulation: Insights from the Peki Community, Volta Region, Ghana - Ameyibor Orison Elysium; Margaret Makafui Tayviah (E-Journal of Humanities, Arts and Social Sciences)
Generally, taboos denote proscriptions, moral tenets, and, to some appreciable degree, a pedagogical tool. In African traditional societies, taboos indicate what should or should not be done, and how to interact with members of society, the environment, the deities, and the ancestors. These taboos ensure balance and harmony between the deities and the community, among members of society and between the community and nature. Typically, taboos are socio-religious constructs that draw on both traditions as well as religion to function. All societies institute clearly defined taboos to direct community members’ behaviour in line with society’s values. The main purpose of this paper was to study taboos as a control mechanism among the Pekis with the view of outlining some notable taboos in Peki and to assess the present state of taboos in Peki. The study employed the qualitative method of enquiry which was largely underpinned by the phenomenological method of enquiry. Purposive sampling was adopted to collect germane information for the study. The paper discovered that taboos permeate all aspects of life and occupy a central place in the effort of traditional African societies to ensure proper social behaviour within the community. The study proposes that there is an urgent need to develop and deploy policies to serve as a sort of affirmative action to safeguard, harness and modify taboos to suit the demands of our present society without undermining tradition or societal values. This paper contributes to the debate on African Religious Traditions and social control.